(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Poultry products food consumption is consistently increased due to its rich nutritional value. Poultry production is agriculture-based subsidiary business for farmers. Different factors like any kind of disease symptoms, toxic agents, viral infections and many more factors affect the quality of poultry production. The study reveals the systematic framework for analysis of quality of poultry production. This study aims an extensive literature for fuzzy based and data mining method for classification, prioritization of poultry quality decisions against measures to define and validate the novel method and results in data mining. The researcher aims to value the gap to work on model by analysing the literature of poultry disease detection and production quality evaluation using data mining.